1980
DOI: 10.1128/jvi.34.2.490-496.1980
|View full text |Cite
|
Sign up to set email alerts
|

mRNA capping enzymes are masked in reovirus progeny subviral particles

Abstract: We examined the enzyme activities associated with progeny subviral particles isolated from L-cells infected with reovirus at 12 h postinfection. Activities normally present in reovirus cores were also found to be present in the progeny subviral particles, with the exception of the capping enzymes. The methylase and guanyl transferase activities, which constitute the capping system, were present in a masked form that could be activated by chymotrypsin digestion. The appearance of these progeny subviral particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…7). Viral RNA is transcribed at two stages of reovirus replication, i.e., (i) during entry, by cores formed from incoming viral particles to generate primary transcripts, and (ii) during assembly, by progeny cores to generate secondary transcripts (29)(30)(31)(32). Transcriptional activity following entry of the virus into cells correlates with loss of the outer capsid.…”
Section: Discussionmentioning
confidence: 99%
“…7). Viral RNA is transcribed at two stages of reovirus replication, i.e., (i) during entry, by cores formed from incoming viral particles to generate primary transcripts, and (ii) during assembly, by progeny cores to generate secondary transcripts (29)(30)(31)(32). Transcriptional activity following entry of the virus into cells correlates with loss of the outer capsid.…”
Section: Discussionmentioning
confidence: 99%
“…Nascent viral cores function as secondary transcriptase particles that continue to synthesize positivesense RNAs (7). The guanylyltransferase and methyltransferase activities in secondary cores are inhibited, and viral mRNAs synthesized from these particles are uncapped (20). Late in infection, uncapped reovirus mRNAs are translated with much greater efficiency than capped viral mRNAs (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The guanylyltransferase and methyltransferase activities in secondary cores are inhibited, and viral mRNAs synthesized from these particles are uncapped (20). Late in infection, uncapped reovirus mRNAs are translated with much greater efficiency than capped viral mRNAs (20)(21)(22). As replication proceeds, VFs enlarge as additional viral RNAs and proteins are produced and incorporated into the structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millward and co-workers have reported (34,35,40) that transcripts synthesized late in the infection by human reovirus progeny virions lack a 5'-terminal cap, while transcripts synthesized by infecting parental virions have a cap. Furthermore, these investigators reported that as the infection proceeds, mRNA translation shifts from a capdependent to cap-independent mode (33).…”
Section: 500 P9mentioning
confidence: 99%